2020
DOI: 10.1177/2322093720934243
|View full text |Cite
|
Sign up to set email alerts
|

Does Flexibility in Human Resource Practices Increase Innovation? Mediating Role of Intellectual Capital

Abstract: Building on resource-based view theory, this article investigates the impact of human resource practice flexibility (HRPF) on innovation performance with (a) the mediating role of intellectual capital (IC) and (b) moderating role of the industry type (service or manufacturing) of an organisation. We empirically examined the relations using a survey dataset of managers of 257 Indian organisations. We have used the structural equation modelling method for data analysis. Findings of the moderated mediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Since prior studies indicate that firm-size, age of the firm and types of industries have a significant effect on ambidexterity, productivity and firm performance, those variables were controlled in the current study (FitzRoy & Kraft, 2005; Kengatharan, 2019; Kostopoulos et al, 2015; Malik et al, 2017; Raffiee & Coff, 2016). The control variables were dummy coded—firm-size (1 = Small, 2 = Large); Age of the firm (1 = less than 25 (<=25) Years, 2 = More than 25 (>25) Years) and industry (1 = Telecommunication and Hotels, 2 = Banking and Insurance)— and were treated as covariates among themselves and with exogenous variable (firm-specific human capital) and added as predictors of the endogenous variables (ambidexterity, productivity and firm performance) (see Kline, 2015; Patky & Pandey, 2020; Xu & Huang, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Since prior studies indicate that firm-size, age of the firm and types of industries have a significant effect on ambidexterity, productivity and firm performance, those variables were controlled in the current study (FitzRoy & Kraft, 2005; Kengatharan, 2019; Kostopoulos et al, 2015; Malik et al, 2017; Raffiee & Coff, 2016). The control variables were dummy coded—firm-size (1 = Small, 2 = Large); Age of the firm (1 = less than 25 (<=25) Years, 2 = More than 25 (>25) Years) and industry (1 = Telecommunication and Hotels, 2 = Banking and Insurance)— and were treated as covariates among themselves and with exogenous variable (firm-specific human capital) and added as predictors of the endogenous variables (ambidexterity, productivity and firm performance) (see Kline, 2015; Patky & Pandey, 2020; Xu & Huang, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The companies that offer more FL for work-life balance, results in a greater competitive advantage (Palm et al, 2020). Sustainable practices in FL results in long-term careers and healthier life as well (Patky and Pandey, 2020). The FL practices give more time to the employees for their skill development.…”
Section: Hypotheses Development and Research Model 31 Sustainable Hum...mentioning
confidence: 99%
“…As stated by Gomezelj Omerzel and Smolčić Jurdana [16], this concept includes not just traditional schooling and academic training but also knowledge and practical experience, most often picked up on the job. Competence, creativity, intuition, and wisdom are also viewed by Patky and Pandey [24] as components of HC, while StC is identified as the codified expertise and institutionalized knowledge included in and applied through databases, structures, systems, patents, publications, and procedures [25]. Employees cannot take these resources with them when they leave the organization because they are the property of the company [3].…”
Section: Intellectual Capital (Ic)mentioning
confidence: 99%
“…Additionally, they demonstrated the close association between innovation and growth. Patky and Pandey [24] concluded that "human resource practice flexibility" is positively correlated with "innovation performance". According to the findings of another study conducted by Ali et al [23], IC and a mediator innovation are key indicators in the increased level of university performance in Pakistan.…”
Section: Intellectual Capital and Organizational Innovationmentioning
confidence: 99%